2014
DOI: 10.1007/s10654-014-9900-9
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia and brain tumors among children after radiation exposure from CT scans: design and methodological opportunities of the Dutch Pediatric CT Study

Abstract: Computed tomography (CT) scans are indispensable in modern medicine; however, the spectacular rise in global use coupled with relatively high doses of ionizing radiation per examination have raised radiation protection concerns. Children are of particular concern because they are more sensitive to radiation-induced cancer compared with adults and have a long lifespan to express harmful effects which may offset clinical benefits of performing a scan. This paper describes the design and methodology of a nationwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
3
26
0
1
Order By: Relevance
“…The upcoming European Epidemiologic Study to Quantify Risks for Pediatric Computed Tomography and to Optimize Doses (EPI-CT) study, which was designed to include approximately 1 million children exposed to CT, will offer opportunities to better address these limitations of the uncertainties induced by incomplete dosimetry (21). (20,21). Studies published before 2014 (6)(7)(8) showed potential evidence of a dose-response relationship between pediatric CT and risk for brain tumor and leukemia, which are the most common radiation-induced neoplasms among children (Table 1).…”
Section: Why We Must Reduce Radiation Dosementioning
confidence: 99%
“…The upcoming European Epidemiologic Study to Quantify Risks for Pediatric Computed Tomography and to Optimize Doses (EPI-CT) study, which was designed to include approximately 1 million children exposed to CT, will offer opportunities to better address these limitations of the uncertainties induced by incomplete dosimetry (21). (20,21). Studies published before 2014 (6)(7)(8) showed potential evidence of a dose-response relationship between pediatric CT and risk for brain tumor and leukemia, which are the most common radiation-induced neoplasms among children (Table 1).…”
Section: Why We Must Reduce Radiation Dosementioning
confidence: 99%
“…Five epidemiologic studies on cancer following radiation exposure from pediatric computed tomography (CT) scans have shown elevated risks of leukemia and brain tumors (1)(2)(3)(4)(5) and other studies are under way (6,7). These studies are record-linkage cohort studies on large numbers of patients collected from existing databases (health insurances and hospitals) with limited or no information on potential confounding factors, which may bias the radiation-cancer association.…”
Section: Introductionmentioning
confidence: 99%
“…We found our method is highly efficient in large-scale dose calculations for CT patients and is more accurate than the ImPACT dosimetry tool although Monte Carlo transport calculations based on real patient CT images may provide more accurate individualized organ doses. We have successfully applied this method to a variety of CT-related studies including retrospective epidemiological study (1,5,18,19) and CT dose trend analysis studies (3,20). …”
Section: Discussionmentioning
confidence: 99%